Regimes especiais substantivos de tributação do ICMS - Andre Sales Moreira (2018)
The dissertation has as object of investigation the special substantive regime of ICMS (Brazilian tax on the circulation of goods, interstate and intercity transportation and communication services), the main tax on consumption in the country. It is observed that these regimes are part of the day-to-day legal universe of the states in Brazil and directly affect the taxpayers located in its territory and elsewhere. Special regimes will be seen and studied in their species. First, a general overview of how the ICMS works will be done. The discussion on the ICMS matrix rule and regimes will also be made objectively. Afterwards, this will be the question of tax justice, that is, in what sense special regimes can be rethought as a way of obtaining it. Following the development of the dissertation, focusing on an economic bias, the fiscal war that permeates ICMS taxation in the country will be discussed and the issue of the notorious Brazil cost will be discussed in a brief manner. Afterwards, a strong criticism will be made regarding the institute studied. This will be followed by an examination of new legislation which concerns the subject matter of the study and the indispensable requirements for the special regimes to have legal validity. Finally, and as a conclusion, in the final considerations, the defense of the substantive special regimes will be synthesized and their legality defended.